Updating Ecological and Behavioral Aspects of the Sandfly Fauna in the Vale do Ribeira Region, São Paulo State, Brazil - Byara Freitas Guedes Oliveira (MDPI AG, 2021)
Some ecological parameters and the distribution of vectors in the municipality of Eldorado, Vale do Ribeira Region, São Paulo, were studied. Entomological surveys were carried out from September 2019 to March 2021. It was observed that a few ecological parameters, including richness, abundance, diversity, and equitability, were typical of a modified environment, where artificial ecotopes maintain the presence of sandflies throughout the year. A total of 11,668 sandflies were captured. The presence of five taxa were observed in Eldorado, with low diversity and high dominance of Nyssomyia intermedia next to Ny. neivai, which are sympatric species. The results presented reinforce the importance of these species in anthropized areas in the transmission of cutaneous leishmaniasis (CL) agents and the need for entomological monitoring. Psathyromyia pascalei was encountered for the first time in the municipality, expanding the known area of distribution of this species in a modified environment.